Reflectance confocal microscopy for diagnosising keratinocyte skin cancers in adults - Dinnes, Jacqueline; Deeks, Jonathan J.; Chuchu, Naomi; Saleh, Daniel; Bayliss, Susan E.; Takwoingi, Yemisi; Davenport, Clare; Patel, Lopa; Matin, Rubeta N.; O'Sullivan, Colette; Patalay, Rakesh; Williams, Hywel C. (Wiley, 2018)
Background Early accurate detection of all skin cancer types is important to guide appropriate management and to improve morbidity and survival. Basal cell carcinoma (BCC) is usually a localised skin cancer but with potential to infiltrate and damage surrounding tissue, whereas squamous cell carcinoma (cSCC) and melanoma are higher risk skin cancers with the potential to metastasise and ultimately lead to death. When used in conjunction with clinical or dermoscopic suspicion of malignancy, or both, reflectance confocal microscopy (RCM) may help to identify those eligible for non-surgical treatment without the need for a diagnostic biopsy, particularly in people with suspected BCC. Any potential benefit must be balanced against the risk of any misdiagnoses. Objectives 1) To determine the diagnostic accuracy of RCM for the detection of BCC, cSCC, or any skin cancer in adults with a) suspicious lesion and b) lesions that are difficult to diagnose (equivocal); and 2) to compare its accuracy with that of usual practice (visual inspection or dermoscopy, or both).